A fÍsica de partÍculas elementares e o Prêmio Nobel de física 2008 - Pleitez, V. [UNESP] (Soc Brasileira Fisica, 2008)
The 2008 Nobel prize of physics pay tribute to three theoretical physicist by their work related to some symmetries of Nature. We briefly comments the importance of these works and the context in which they were done.
The elementary particle physics and the 2008 Nobel Prize of physics